Pengaruh Risk Management Terhadap Corporate Performance di Mediasi Oleh Internal Control Dan Corporate Governance - Teddi Gunadi (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2022)
Based on research and discussion of this study, the researcher provides advice relating to management that is practical. In this case maximizing the risk management function in improving the company's performance. If any risk can be mitigated properly, it can minimize the impact caused, protect from risks that can hamper the achievement of company goals. The research used is quantitative research with descriptive methods and causality. This aims to describe research in accordance with reality without subjectivity. With a sample of 200 respondents. Testing using SEM analysis, where obtained for the value of R2 functions to indicate how much each independent variable is able to explain the dependent variable. Performance Management has R2 of 0.92. This figure shows that Risk Management, Internal Control and Good Corporate Governance can explain 92% of variants of performance management, while the rest is explained by other factors. For the value of R2 functions to show how much each independent variable is able to explain the dependent variable. Internal control has R2 of 0.82. This figure shows that risk management can explain 82% of variants of internal control, while the rest is explained by other factors. For the value of R2 functions to show how much each independent variable is able to explain the dependent variable. Good Corporate Governance has R2 of 0.82. This figure shows that risk management can explain 82% of variants of good corporate governance, while the rest is explained by other factors.